“Arts Once More United”: Bridging Disciplines through Creative Media Research, Toronto, 1953–55 - Darroch, Michael (Intermédialités / Intermediality)

(untitled) (Revue intermédialités (Presses de l’Université de Montréal), 2017)
From 1953 to 1955, the Ford Foundation funded a unique experiment in intermedial study and experimentation at the University of Toronto. The Culture and Communications Seminar and the journal Explorations, led by Edmund Carpenter, Marshall McLuhan, and Jaqueline Tyrwhitt, are indicative of the ways in which intermedial studies became organized and institutionalized in the 1950s and 1960s. The scholarly network that took shape during these years of Ford Foundation funding laid the framework in Canada for initiatives in creative media research that have become fundamental aspects of arts and humanities education. This article charts the assemblage of geographic, disciplinary, artistic, and organizational connections that facilitated this educational experiment.